Effects of Advanced Platelet Rich Fibrin (A-PRF+), Enamel Matrix Derivative (EMD) and Open Flap Debridement on clinical and wound healing parameters in molar furcation sites: A case series from a RCT study - Pitzurra, L.; Vasdravellis, D.; Rosema, N.A.M.; Bizzarro, S.; Loos, B.G. (Frontiers in Dental Medicine, 2023)
Aim To study the effects of advanced platelet-rich fibrin (A-PRF+) and enamel matrix derivative (EMD) compared to open flap debridement (OFD) alone in molar furcation sites grade II on clinical and wound healing parameters. Materials and methods A randomized controlled trial was designed. Eligible patients were randomly allocated to one of three treatment groups: A-PRF+, EMD or OFD. The patients and clinical examiners were blinded for the treatment received. A minimally invasive microsurgical approach was performed for the three modalities. Clinical measurements were scored at baseline and 6 months post-operatively. The clinical healing of each furcation was scored via the Early Wound Healing Index on day 3, 1 week, 2 weeks and 6 weeks. Results 17 patients (A-PRF+ n = 6, EMD n = 5, OFD n = 6) completed the 6 months of follow-up. The further completion of the trial had to be cancelled due to the COVID-19 pandemic. In three patients in the A-PRF+ group, the grade II of the treated furcation regressed to grade I; the corresponding number in the EMD and OFD groups was zero and one respectively. Further, 3, 1 and 4 patients in the PRF, EMD and OFD groups respectively, showed a gain of bone level ≥1 mm. The defects in the A-PRF+ group showed delayed early healing compared to the EMD and OFD groups. Conclusion The case series (RCT design) suggests a slight advantage for A-PRF+ over EMD and OFD, regarding the regressing of a furcation II to grade I; however this treatment showed delayed early wound healing compared to EMD or OFD. Clinical Trial Registration https://www.isrctn.com/, identifier ISRCTN13520922.